2017
DOI: 10.1111/ced.13352
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunoglobulin for the treatment of deep morphoea in a child

Abstract: Morphoea, also known as localized scleroderma, is a disorder characterized by excessive collagen deposition leading to thickening of the dermis and/or subcutaneous tissues. Intravenous IgG therapy has induced improvement in some fibrotic conditions. The primary indication for subcutaneous IgG (SCIG) is in primary immunodeficiency disorders as replacement therapy; however, recently there has been considerable interest in SCIG as an immunomodulatory agent. We report an 11-year-old girl with deep morphoea who was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(29 reference statements)
0
4
0
5
Order By: Relevance
“…24 Deep morphea primarily affects the subcutaneous cellular tissue, and produces extensive sclerosis and hyalinization, which extends to the underlying fascia. 25…”
Section: Histopathologymentioning
confidence: 99%
“…24 Deep morphea primarily affects the subcutaneous cellular tissue, and produces extensive sclerosis and hyalinization, which extends to the underlying fascia. 25…”
Section: Histopathologymentioning
confidence: 99%
“…Literature also incudes paper on the use of immunoglobulins administered subcutaneously (subcutaneous immunoglobulin -SCIG) in the treatment of deep localized scleroderma [37]. Yamazaki-Nakashimada et al reported that a two-month SCIG therapy (1.6 g twice a week) in an 11-year-old patient resulted in clinical and histopathological improvements not Zgodnie ze stanowiskiem CARRA (Childhood Arthritis and Reumatology Research Alliance) MTX może być stosowany w monoterapii lub w skojarzeniu z GKS przyjmowanymi doustnie lub dożylnie [9,13,15,26].…”
Section: Postać Dziecięca Twardziny Ograniczonej O Ciężkim Przebiegumentioning
confidence: 99%
“…opisali przypadki pacjentów z twardziną ograniczoną zniekształcającą głęboką i linijną, nieskutecznie leczonych konwencjonalnymi metodami (GKS, MTX, MMF), u których zastosowano TCZ w schemacie 8 mg/kg (masa ciała ≥ 30 kg) lub 12 mg/kg (masa ciała ≤ 30 kg) w 0, 2. i 4. tygodniu, a następnie w odstępach 4-tygodniowych [35,36]. Po średnio 12-25 miesiącach leczenia stwierdzono znaczą-Dermatology Review/Przegląd Dermatologiczny 2020/2 only within the foci that had been subject to injections, but also within other exanthems [37].…”
Section: Postać Dziecięca Twardziny Ograniczonej O Ciężkim Przebieguunclassified
See 2 more Smart Citations